A ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN PENGASPALAN JALAN KEUDE BIREM - ALUR TEH KECAMATAN BIREM BAYEUN ACEH TIMUR - RUSDI MAULANA; Bravikawati, Marini; Basrin, Defry; Mutia, Eeka (Jurnal Media Teknik Sipil Samudra, 2025)
Road paving works play a critical role in supporting economic growth and public welfare, as mandated by Government Regulation No. 34/2006. However, the implementation of such projects is often hindered by road damage and the limited availability of heavy equipment and skilled operators. This study aims to identify the types of heavy equipment used, calculate their production capacity, and analyze the duration of major construction phases. The method applied is time study, using primary data collected from field surveys and secondary data from supporting documents such as construction drawings and literature. The results indicate that each type of equipment showed varying levels of productivity deviation between planning and actual implementation. Dump trucks increased in productivity from 2.98 m³ to 3.49 m³, while motor graders decreased from 366.18 m³ to 317.475 m³. Significant increases were observed in the vibrator roller and air compressor, whereas asphalt finisher, tandem roller, and pneumatic tired roller experienced substantial drops in productivity. The asphalt sprayer maintained consistent performance at 4.980 liters/hour. In conclusion, heavy equipment productivity is significantly influenced by equipment type, field conditions, and operational coordination, all of which are crucial to ensuring timely project completion with quality standards met.